2022
DOI: 10.1109/jstars.2022.3187107
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-Phase CNN-Based SAR Target Classification via Complex-Valued Sparse Image

Abstract: It is known that a synthetic aperture radar (SAR) image obtained by matched filtering (MF)-based algorithms always suffers from serious noise, sidelobes, and clutters. However, the improvement of the image quality means the complexity of the SAR system will increase, which affects the application of the SAR image. The introduction of the sparse signal processing technique into SAR imaging proposes a new way to solve this problem. Sparse SAR image obtained by sparse recovery algorithms shows a better image perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recent works have concentrated on employing complex-valued learning models to solve radar imaging tasks. For instance, in [43], an Amplitude Phase CNN (AP-CNN) was formulated to classify targets using radar image amplitude and phase information. This approach showcased substantial classification accuracy improvements even with smaller training datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Recent works have concentrated on employing complex-valued learning models to solve radar imaging tasks. For instance, in [43], an Amplitude Phase CNN (AP-CNN) was formulated to classify targets using radar image amplitude and phase information. This approach showcased substantial classification accuracy improvements even with smaller training datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the widespread adoption of this strategy, it is challenging to pinpoint a model that's intricately tailored for SAR images, as most are honed for publicly available data sets rather than the unique characteristics of SAR imagery. Recognizing this gap, several researchers have proposed models meticulously optimized for SAR image classification, aiming to enhance the precision and reliability of automated systems in processing and interpreting SAR imagery [3], [10], [15]- [25].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [3] proposed a domain adaptation-based method using heterogeneous features to overcome the vulnerability of noise from the A-ConvNets method. Deng et al [15] developed an amplitude-phase CNNs (AP-CNN), utilizing amplitude and phase data from sparse images, enhanced by a bi-iterative soft thresholding (BiIST) algorithm to improve quality. This approach improved classification accuracy more than traditional amplitude-based methods, especially with limited training data.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], it was shown that many filters in image processing tasks, such as matched filter and image restoration can be effectively designed if both the magnitude and phase specifications are included. In [11], a classification algorithm, Amplitude Phase-CNN (AP-CNN), was developed based on the amplitude and phase of sparse Synthetic Aperture Radar (SAR) images. The AP-CNN model used both the amplitude and phase of the SAR images for training, which improved the classification accuracy of the model.…”
Section: Introductionmentioning
confidence: 99%